Patent applications - Structures, trends and recent developments 2021 - Peter Neuhäusler; Oliver Rothengatter (Expertenkommission Forschung und Innovation (EFI), 2022)
In this study, we contribute to the evaluation of the performance of the German science and research system by analyzing the dynamics of transnational patent filings of German inventors in an international comparison over the past 20 years. Besides country-specific analyses, we further differentiate our findings by 38 high-technology fields including aggregate categories (high-level, leading-edge and less R&D intensive technologies). In addition to country comparisons, which are analyzed in each years' report of this series, we also provide international co-patenting trends, dig deeper into regionalized patent statistics by analyzing patent activities of the German federal states. In a final step, we take a closer look at patent dynamics in the public research sector.
Keywords: 330; Patent; Hochtechnologie; Internationale Zusammenarbeit; Universitäre Forschung; Forschungseinrichtung; Teilstaat; Deutschland; Welt